Underground Transfer of Floods for Irrigation (UTFI): exploring potential at the global scale - Alam, Mohammad Faiz; Pavelic, Paul (International Water Management Institute, 2020)
This report presents a spatial analysis conducted at global scale to identify areas of high suitability for implementing the Underground Transfer of Floods for Irrigation (UTFI) approach. The study used multiple global spatial datasets, and the related data were arranged under three categories – water supply, water demand and water storage – to assess global UTFI suitability. Among the river basins with high suitability, the Awash in Ethiopia, Ramganga in India (one of the major tributaries of the Ganges River Basin) and Chao Phraya in Thailand were selected for the economic analysis in this study. The results from this study are intended to provide a first step towards identifying the broad areas (at the river basin or country scale) where more detailed investigation would be worthwhile to ascertain the technical and economic feasibility of UTFI, with greater confidence.